2014
DOI: 10.3802/jgo.2014.25.3.206
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided conformal brachytherapy of cervix cancer: survival, patterns of failure, and late complications

Abstract: ObjectiveThe aim of this study was to report on the long-term results of transabdominal ultrasound guided conformal brachytherapy in patients with cervical cancer with respect to patterns of failures, treatment related toxicities and survival.MethodsThree hundred and nine patients with cervical cancer who presented to Institute between January 1999 and December 2008 were staged with magnetic resonance imaging and positron emission tomography and treated with external beam radiotherapy and high dose rate confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 25 publications
(34 reference statements)
1
59
0
Order By: Relevance
“…Presently, most series are limited to small numbers of patients and use of variable imaging techniques (Table 4). Outcomes appear exceptionally favorable using IBBT, with local control ranging from 78.5% to 100.0% (10,(14)(15)(16)(17)(18)(23)(24)(25). Our study adds to the IBBT body of literature by providing the largest North American experience and one of the largest series using MRI-based planning, showing similarly excellent local control rates (91.6%) and low rates of late grade 3 or greater toxicity (0.9%).…”
Section: Discussionsupporting
confidence: 56%
“…Presently, most series are limited to small numbers of patients and use of variable imaging techniques (Table 4). Outcomes appear exceptionally favorable using IBBT, with local control ranging from 78.5% to 100.0% (10,(14)(15)(16)(17)(18)(23)(24)(25). Our study adds to the IBBT body of literature by providing the largest North American experience and one of the largest series using MRI-based planning, showing similarly excellent local control rates (91.6%) and low rates of late grade 3 or greater toxicity (0.9%).…”
Section: Discussionsupporting
confidence: 56%
“…The latest report by Narayan et al (25) also showed promising clinical results. Three hundred nine patients with cervical cancer were treated between January 1999 and December 2008 with external beam radiotherapy and HDR conformal TAUS-guided BT with curative intent.…”
Section: Discussionmentioning
confidence: 78%
“…Local failure rates according to FIGO Stage I, II, and III were 12%, 10%, and 17%, respectively. In toxicity profiles, the rate of Grade 3e4 toxicities of bladder, rectum, and vagina was 0.3, 0.99, and 0.69 per 100 person-years of FU, respectively (25).…”
Section: Discussionmentioning
confidence: 99%
“…All had used MRI based conformal brachytherapy using GEC-ESTRO recommendation. Kailash Narayan et al (15) concluded that real-time imaging and treatment planning using USG would make this a method of choice for treating cancer cervix in most parts of the world where cancer cervix remains a major health problem and MRI is inaccessible.…”
Section: Tod Et Al Formulated the Manchester System In 1938mentioning
confidence: 99%